Два диалога с ветром (лексико-семaнтический анaлиз стихотворений Ф. Тютчева и Н. Рубцова) - Кудрявцев, М. В. (Kalbotyra, 1990)
The paper presents a comparative analysis or the poetic languages of two poems by two Russian poets: Tyutchev and Rubtsov. The poems have the same underlying image or the wind and are based on the dialogue between the “lyrical hero” and the “wind”. The analysis or lexico-semantic and syntactical peculiarities of the given texts enables the investigator to establish the typological affinities and differences in the artistic model of the world of each poet. The man’s relationship with nature and its alienation are two dominant features which determine the world outlook not only of the poets, but also of their epochs – the 19th and the 20th centuries.